2000
DOI: 10.1002/(sici)1097-4636(200004)50:1<82::aid-jbm12>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cell sheet detachment from Poly(N-isopropylacrylamide)-grafted porous cell culture membranes

Abstract: Fabrication of functional tissue constructs using sandwiched layers of cultured cells could prove to be an attractive approach to tissue engineering. Rapid detachment of cultured cell sheets is a very important recovery method that permits facile manipulation of the sheet and prevents functional damage. To accelerate the required culture substrate hydrophilic and hydrophobic structural changes in response to culture temperature alteration, poly(N-isopropylacrylamide) (PIPAAm) was grafted onto porous culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(137 citation statements)
references
References 27 publications
2
134
0
1
Order By: Relevance
“…Therefore, the conclusion drawn in the PCA model is only valid for this range of contact angles. The higher contact angles (close to 71.2°) are similar to that of TCPS [39], which is known to be suitable for most cell cultures and may be approximately the optimal contact angles for maintaining DC immature state. However, close inspection of Table 3 indicated that no strong correlation exists between DC maturation and contact angle, but pMAs with higher contact angles do group towards the left of Table 3 with pMAs such as pHEMA and pHPMA that caused low DC maturation.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the conclusion drawn in the PCA model is only valid for this range of contact angles. The higher contact angles (close to 71.2°) are similar to that of TCPS [39], which is known to be suitable for most cell cultures and may be approximately the optimal contact angles for maintaining DC immature state. However, close inspection of Table 3 indicated that no strong correlation exists between DC maturation and contact angle, but pMAs with higher contact angles do group towards the left of Table 3 with pMAs such as pHEMA and pHPMA that caused low DC maturation.…”
Section: Discussionmentioning
confidence: 84%
“…6(B)]. 64 To this end, we grafted PIPAAm on a porous PET membrane by electron beam-irradiated polymerization of IPAAm. The graft density of PIPAAm was 1.4 ÎŒg/cm 2 on porous membrane while that on the control TCPS surface was 1.6 ÎŒg/cm 2 , demonstrating that almost identical graft density could be obtained.…”
Section: Porous Membranementioning
confidence: 99%
“…Their ability to contain water, stability in aqueous media and softness, makes hydrogels compatible with biological systems and thus they were proposed for different biomedical applications such as tissue engineering, cell adhesion, wound healing, controlled drug release, contact lenses, to name a few [3,4,5,6,7,8,9,10,11]. Hydrophilic polymer layers were also employed as support for lipid bilayer membranes, in particular for electric measurements of transport phenomena involving membrane proteins [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%